First Aid For Accidents Knowledge Level Of Students at Budi Murni 2 Catholic Private High School Medan 2023 - Indra Hizkia P., S.Kep., Ns., M.Kep; Floresta Br Sitepu, S. Kep, Ns, .M.Psi; Sara Meilani Sihombing (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
First Aid in Accidents is a program designed to provide emergency care and treatment to accident victims before they are taken to a hospital, health facility, or clinic where they can receive further medical care from a doctor or paramedic. If an accident or injury is not handled properly, it can develop into an emergency, resulting in serious injury and even death. First aid training and knowledge is very important for dealing with accidents because it teaches basic methods for saving victims from accidents and disasters that occur. This is so that with adequate preparation, such as basic life support training, reaction actions will be faster and more accurate, minimizing the number of victims and damage. The study's goal is to ascertain how